Influence of 6-aminonicotinamide (6AN) on Leishmania promastigotes evaluated by metabolomics: Beyond the pentose phosphate pathway. (1st October 2018) - Almugadam, Shawgi Hago; Trentini, Alessandro; Maritati, Martina; Contini, Carlo; Rugna, Gianluca; Bellini, Tiziana; Manfrinato, Maria Cristina; Dallocchio, Franco; Hanau, Stefania
Abstract: 6-Aminonicotinamide (6AN) is an antimetabolite used to inhibit the NADPH-producing pentose phosphate pathway (PPP) in many cellular systems, making them more susceptible to oxidative stress. It is converted by a NAD(P) + glycohydrolase to 6-aminoNAD and 6-aminoNADP, causing the accumulation of PPP intermediates, due to their inability to participate in redox reactions. Some parasites like Plasmodium falciparum and Coccidia are highly sensitive but not all cell types showed a strong responsiveness to 6AN, probably due to the different targeted pathway. For instance, in bacteria the main target is the Preiss-Handler salvage pathway for NAD + biosynthesis. We were interested in testing 6AN on the kinetoplastid protozoan Leishmania as another model to clarify the mechanisms of action of 6AN, by using metabolomics. Leishmania promastigotes, the life-cycle stage residing in the sandfly, demonstrated a three order of magnitude higher EC50 (mM) compared to P. falciparum and mammalian cells (μM), although pre-treatment with 100 μM 6AN prior to sub-lethal oxidative challenge induced a supra-additive cell kill in L. infantum . By metabolomics, we did not detect 6ANAD/P suggesting that NAD + glycohydrolases in Leishmania may not be highly efficient in catalysing transglycosidation as happens in other microorganisms. Contrariwise to the reported effect on 6AN-treated cancer cells, we did not detect 6-phosphogluconate (6 PG) accumulation, indicating that 6ANADP cannot bind with high affinity to the PPP enzyme 6 PG dehydrogenase. By contrast, 6AN caused a profound phosphoribosylpyrophosphate (PRPP) decrease and nucleobases accumulation confirming that PPP is somehow affected. More importantly, we found a decrease in nicotinate production, evidencing the interference with the Preiss-Handler salvage pathway for NAD + biosynthesis, most probably by inhibiting the reaction catalysed by nicotinamidase. Therefore, our combined data from Leishmania strains, though confirming the interference with PPP, also showed that 6AN impairs the Preiss-Handler pathway, underlining the importance to develop compounds targeting this last route. Highlights: In Leishmania 6AN was cytostatic at higher concentration than mammal cells. In promastigotes 6AN caused profound PRPP decrease and nucleobases accumulation. The treatment with 6AN induced a significant nicotinate depression. 6AN by inhibiting nicotinamidase impairs the salvage NAD + pathway beyond PPP.